International language volapük (wolapik) — career and barrier - Kotlarska, Irmina (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The aim of this article is to present Polish textbooks for learning the language of volapük published in the 1980s as texts promoting the forgotten idea of using an international auxiliary language called volapük. Methodologically, the article is in the area of pragmatically oriented diachronic linguistics. The linguistic view was subjected to four textbooks published between 1888 and 1889. Their authors were convinced of the need to popularize the language of volapük in Polish lands, and based their belief on the arguments underlying the movement of volapükists. The desire to win supporters for the idea of using an international auxiliary language influenced the style and language of the textbooks being observed. Linguistic tools for communicating knowledge about the new language (didactic function) and those that were supposed to persuade Poles to learn the international language (persuasive function) were presented.